Penguatan Karakter dan Mentalitas Siswa Melalui Program Pondok Ramadhan di SMAN 1 Plemahan - Shivy Indah Novisari; Ericha Lisa Wibowo; Chintia Dewi Basuki; Mukhamad Rinda Rifa’i; Mohammad Sulkifli (Fakultas Tarbiyah dan Ilmu Keguruan UIN Syekh Wasil Kediri, 2026)
This community service activity aims to strengthen the character and mental resilience of senior high school and vocational students through a guest lecturer program integrated into the Ramadan boarding school (Pondok Ramadhan) activities. The background of this program is based on the increasing need to develop students’ character, discipline, and mental readiness in facing future challenges, which are not yet fully addressed in formal education. This study employs a Participatory Action Research (PAR) approach, consisting of problem identification, planning, implementation, evaluation, and reflection stages. The program was conducted through interactive lectures, group discussions, and reflective sessions incorporating spiritual values relevant to the Ramadan context. The results indicate an improvement in students’ understanding of character values, increased learning motivation, and greater awareness of discipline and responsibility. In addition, students demonstrated high levels of enthusiasm and active participation throughout the program. This activity contributes to the holistic development of students by integrating cognitive, affective, and spiritual dimensions. Therefore, the guest lecturer program within the context of Ramadan activities can serve as an effective and contextual model of community engagement in supporting character development among youth.